THE EFFECT OF SELECTED MACRO-ECONOMİC INDİCATORS ON THE FREQUENCY OF INİTİAL PUBLİC OFFERİNGS: A RESEARCH ON THE G-7 COUNTRİES (Third Sector Social Economic Review, 2022)
The main objective of this study is to investigate effects of macroeconomic indicators on IPO wave. In this study, the relationship between macroeconomic indicators and frequency of the ini-tial public offerings in a given country are examined. Macroeconomic indicators such as Gross Domestic Product (GDP), Net Portfolio Investments (NPI) and Net Foreign Direct Investment (NFDI) are used as independent variables. All data have been obtained from the World Bank for the widest possible date range. Analyzes are performed for 1999-2020 period based on the data set consisting of the public offerings frequency and macroeconomic indicators of the G-7. Panel data method is applied in the analysis. According to the results of the cross-section dependency test, it has been determined that there is a cross-section dependence between the series in the model. Therefore, the Peseran (2007) unit root test, which takes into account the cross-sectional dependence of the stationarity of the series, is applied. For model estimation, fixed and fixed-trend models are applied to all dependent and independent variables. According to results of the analy-sis, it has been determined that the GDP, NPI and NFDI in the model do not have a statistically significant effect on the public offering frequency. According to the findings obtained from the study, it can be concluded that the companies do not consider these indicators when timing the IPO. Developing the scope of this study by applying it on different developed and developing country groups comparatively is recommended to researchers working in this field in order to obtain more meaningful and comprehensive findings.
Keywords: Initial Public Offering; GDP; Net Portfolio Investments; Net Foreign Direct Investments; Panel Data